(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aims to investigate the awareness level among school teachers of their students’ cybersecurity. The teachers’ perception of their students’ cybersecurity awareness was examined based on a case study of the emirate of Ajman private schools in UAE. A survey was conducted of a sample of school teachers at 29 private schools in Ajman. Stratified random sample for schools in the Emirate of Ajman have been used and then a systematic random sample of 172 teachers in the schools were chosen as the target population representation. Results of the study indicate that the level of awareness of school teachers towards their students’ protection and safety in 13 variables that had been studied is increased and this awareness has decreased in eight other variables, the study also reveals that there is a statistically significant relationship between the variable of specialization, and teachers’ awareness towards their students’ cybersecurity driven mainly by the signiﬁcant differences between the average responses of mathematics teachers and the Arabic language in favor of mathematics teachers, and the difference between the average responses of social science teachers and the Arabic language in favor of social science teachers, and the difference between the average responses of social science teachers and the English language in favor of social science teachers.